2020
DOI: 10.1177/0885066620960626
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fluid Balance on Mortality Is Mediated by Fluid Accumulation Index in Sepsis: A Cohort Study

Abstract: Fluid balance (FB) is associated with poor sepsis outcomes; however, it cannot accurately reflect the dynamic fluid accumulation status. Here, we explored a new index, the FB to fluid intake ratio (FB/FI), for evaluating dynamic fluid accumulation in sepsis. FB/FI values within 48 hours were recorded. Their association with in-hospital mortality was investigated using logistic regression and mediation analyses of data from 7,839 patients. In extended logistic models, a linear association was found between FB a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…However, these two variables may be correlated to each other; thus, their separate analysis without adjustment might result in the overestimation of their significance. The definition of FAI was first introduced in the analysis of fluid management by Shen et al, who consequently found that the impact of FB on mortality is mediated by FAI in patients with sepsis ( 9 ). Our pooled FB, FI, and FAI analysis using multivariable logistic regression also showed that FAI, but not FB, was significantly associated with in-hospital mortality, after adjusting for confounding factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these two variables may be correlated to each other; thus, their separate analysis without adjustment might result in the overestimation of their significance. The definition of FAI was first introduced in the analysis of fluid management by Shen et al, who consequently found that the impact of FB on mortality is mediated by FAI in patients with sepsis ( 9 ). Our pooled FB, FI, and FAI analysis using multivariable logistic regression also showed that FAI, but not FB, was significantly associated with in-hospital mortality, after adjusting for confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…This retrospective cohort study aimed to explore the association between fluid management and in-hospital mortality in patients with sepsis and concomitant HF, as well as to find a better indicator to guide fluid management among FB, fluid intake (FI), and the fluid intake ratio (FB/FI), which is called the fluid accumulation index (FAI) and was first introduced by Shen et al ( 9 ). We focused on fluid management within the first 48 h after admission to the ICU and explored the relationship of FI, FB, and FAI with in-hospital mortality in sepsis patients with pre-existing HF.…”
Section: Introductionmentioning
confidence: 99%
“…1, with different fluid intake and capillary leak severity, the fluid balance is the same in patients A and B, while the fluid accumulation index is different (0.4 vs. 0.8). In addition, our previous finding [4] also revealed a complete mediation relationship within fluid balance, fluid balance/fluid intake and mortality in sepsis, which suggested that the association between fluid balance and mortality is completely mediated by fluid balance/fluid intake ratio [5]. Therefore, compared to fluid balance, fluid intake or fluid output alone, the fluid accumulation index (fluid balance/fluid intake) can more accurately reflect the ability to excrete excessive fluid under different fluid loads and predict the prognosis.…”
Section: To the Editormentioning
confidence: 81%
“…Shen et al correctly mention that fluid intake, fluid output and fluid balance have complex interactions, and that a 'fluid accumulation index, ' an index derived from both the fluid balance and the fluid intake, may play a vital role in this association [4].…”
Section: To the Editormentioning
confidence: 99%
“…This is supported by a recent investigation comparing the fluid accumulation index (FAI) to FB. The FAI consists of the ratio of FB to fluid intake as a measure of the patients’ ability to regulate his body water ( 33 ). A retrospective cohort study in HF patients with septic shock demonstrated an association of the FAI with mortality, while there was no association with FB ( 20 ).…”
Section: Discussionmentioning
confidence: 99%